2015
DOI: 10.1016/j.bbamem.2015.03.029
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cholesterol on membrane protein structure, function, and dynamics studied by molecular dynamics simulations

Abstract: The plasma membrane, which encapsulates human cells, is composed of a complex mixture of lipids and embedded proteins. Emerging knowledge points towards the lipids as having a regulating role in protein function. Furthermore, insight from protein crystallography has revealed several different types of lipids intimately bound to membrane proteins and peptides, hereby possibly pointing to a site of action for the observed regulation. Cholesterol is among the lipid membrane constituents most often observed to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
139
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(156 citation statements)
references
References 138 publications
11
139
0
2
Order By: Relevance
“…First, cholesterol may bind specifically with membrane proteins and thereby modulate their conformation and function, or cholesterol may modulate membrane physical properties to match the conditions that promote the activation of a given membrane protein. Related experimental 68, 69 and simulation 7072 data are consistent with this view. Also, as discussed by Sodt et al .…”
Section: Discussionsupporting
confidence: 78%
“…First, cholesterol may bind specifically with membrane proteins and thereby modulate their conformation and function, or cholesterol may modulate membrane physical properties to match the conditions that promote the activation of a given membrane protein. Related experimental 68, 69 and simulation 7072 data are consistent with this view. Also, as discussed by Sodt et al .…”
Section: Discussionsupporting
confidence: 78%
“…Cholesterol is also required to maintain the signaling capacity of lipid rafts (see Simons and Toomre, 2000; Fielding and Fielding, 2004; Grouleff et al, 2015). Sengupta has shown (2012) that cholesterol modulates the depth as well as the orientation of caveolin-1 binding to membranes and that cholesterol stabilizes the more open conformations of caveolin-1.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol appears to be involved in a variety of physiological functions in addition to regulating ion channels and membrane dynamics. Cholesterol may serve both as a steroid hormone precursor in mitochondria (Clark and Stocco, 1996; Miller and Strauss, 1999) as well as structural elements of ion channels and as control elements (Simons and Toomre, 2000; Fielding and Fielding, 2004; Grouleff et al, 2015) in multiple response systems.…”
Section: Discussionmentioning
confidence: 99%
“… suggested that the fluidity of a membrane decreases with an increase in PA content, due to the very small headgroup of PA that leads to the lateral condensation of the lipid tails. Some lipids, such as cholesterol, are known to reduce membrane fluidity , and due to such influence, cholesterol indirectly modulates the function of some membrane proteins , such as cholecystokinin receptor or GABA receptor . But, due to the low content of PA in membranes, the putative ability of PA to affect membrane fluidity should not influence the properties of membrane proteins noticeably.…”
Section: Chemical Properties Of Pamentioning
confidence: 99%